2001
DOI: 10.4141/a00-104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary level of soybean oil and palm oil on apparent ileal amino acid digestibility and postprandial flow patterns of chromic oxide and amino acids in pigs

Abstract: Albin, D. M., Smiricky, M. R., Wubben, J. E. and Gabert, V. M. 2001. The effect of dietary level of soybean oil and palm oil on apparent ileal amino acid digestibility and postprandial flow patterns of chromic oxide and amino acids in pigs. Can. J. Anim. Sci. 81: 495-503. A study was conducted to evaluate the apparent ileal digestibilities of amino acids in pigs (initial weight 78 kg) fed diets supplemented with either soybean or palm oil, at either 100 or 200 g kg -1 diet. A control diet with no added fat was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…These two groups were different not only because of the type of oil or fat but also because of the inclusion level of diet13, which was 3%CPOmix13. The explanation could be supported by the results of Albin et al, (2001) who found that adding high levels of soybean and palm oil to a semi-purified swine diet increased the apparent ileal digestibility of some amino acids. Also, the fat sources affected some apparent ileal amino acid digestibility (Albin et al, 2001), digestible energy and ether extract digestibility (Mitchaothai et al, 2008;Yongbo et al, 2015).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…These two groups were different not only because of the type of oil or fat but also because of the inclusion level of diet13, which was 3%CPOmix13. The explanation could be supported by the results of Albin et al, (2001) who found that adding high levels of soybean and palm oil to a semi-purified swine diet increased the apparent ileal digestibility of some amino acids. Also, the fat sources affected some apparent ileal amino acid digestibility (Albin et al, 2001), digestible energy and ether extract digestibility (Mitchaothai et al, 2008;Yongbo et al, 2015).…”
Section: Methodssupporting
confidence: 74%
“…The explanation could be supported by the results of Albin et al, (2001) who found that adding high levels of soybean and palm oil to a semi-purified swine diet increased the apparent ileal digestibility of some amino acids. Also, the fat sources affected some apparent ileal amino acid digestibility (Albin et al, 2001), digestible energy and ether extract digestibility (Mitchaothai et al, 2008;Yongbo et al, 2015). When fat is oxidized, ADG and ADFI in nursery pigs will decrease; however, free fatty acid (FFA) concentrations of at least 53% in choice, white grease fat does not adversely affect its utilization in nursery pigs (DeRouchey et al, 2004).…”
Section: Methodssupporting
confidence: 74%
“…This result may be related to improvement in the digestibility of crude protein, releasing more amino acids for protein deposition at the expense of fat (Albin et al, 2001). In the case of hot environment, the lower intake made possible by these conditions might have attenuated this effect.…”
Section: Resultsmentioning
confidence: 99%
“…The pigs were fed daily at 09:00 and 16:30 h (08:00 and 20:00 h for 5 days prior to and the 2 days during the ileal digesta collection periods) and given a fixed allowance for the 14-day balance period. According to the method of Albin et al (2001), a 5-day adaptation period to 12 h feeding intervals was sufficient to ensure that diurnal variations did not affect the ileal flow. Feed allowances were 1200, 1500, 1800 and 2100 g/day for the four consecutive balance periods corresponding to approximately 85% of ad libitum intake as calculated by Rao and McCracken (1991).…”
Section: Methodsmentioning
confidence: 99%